Knowledge Brokering: An Innovative Model for Supporting Evidence-Informed Practice in Respiratory Care - Alison M Hoens; W Darlene Reid; Pat G Camp (Canadian Respiratory Journal)
The process of adopting research findings in the clinical setting is challenging, regardless of the area of practice. One strategy to facilitate this process is the use of knowledge brokering. Knowledge brokers (KBs) are individuals who work to bridge the gap between researchers and knowledge users. In the health care setting, KBs work closely with clinicians to facilitate enhanced uptake of research findings into clinical practice. They also work with researchers to ensure research findings are translatable and meaningful to clinical practice. The present article discusses a KB’s role in a respiratory care setting. Working closely with both researchers and clinicians, the KB has led teams in the process of conceptualizing, developing, testing, disseminating and evaluating several projects related to respiratory care, including projects related to mobility in critical care settings and acute exacerbations of chronic obstructive pulmonary disease; inspiratory muscle training; and the use of incentive spirometry in postsurgical populations. The KB role has provided an important communication link between researcher and knowledge user that has facilitated evidence-informed practice to improve patient care.